A Comparative Study on Calculated Work Function of Metals Using Metallic Plasma Model with Stabilized Jellium, Ab-Initio Approach and Experimental Values - Olubosede, O.; Afolabi, O. M.; Oniya, E. O.; Tomiwa, A. C. (New Insights into Physical Science Vol. 13, 2021)
The work function of metals was calculated using the metallic plasma model (MPM). The results obtained were compared with the available results of the stabilized jellium model (SJM), Ab-initio model and the experimental values. Result shows that the stabilized jellium model was in good agreement with experimental values for the simple metals, the transition, inner transition and rare-earth metals. The metallic plasma model gave results that are agreeable with experimental values for most of the metals especially the polycrystalline metals. The work function of elemental metals obtained from the SJM calculation was in fairly good agreement with experimental values. This shows that the SJM could be used to calculate and predict the work function of metals. The ab-initio results were higher than experimental values except for Ba, Ca and Sr, this shows that the metallic plasma model is more reliable in predicting the work function of metals.